Artificial neural network and its Islamic relevance - Ahmad Kamaruddin, Saadi; Ahmed Shogar, Ibrahim Adam (Kulliyyah of Science, IIUM, 2011)
The complex workings and wonders of the human brain have become mysterious since time immemorial. Human brain is a thinking organ that learns and grows by interacting with the world through perception and action; and it is able to continually adapt and rewire itself. Only recently scientists have been able to learn how the neural network of the brain forms. Artificial neural network (ANN) is a mathematical model or computational model that inspired by the structure and functional aspects of biological neural networks. As a final verdict, the complex structure of ANN which resembles the ordinary human brain mechanism may help for better understanding of the creative Power and lead to the enhancement of our faith in God as the Mighty Creator. The objective of this paper is to relate ANN with the Islamic worldview and its relevance for learning and education. The method used was analytical outlook to comprehend ANN in an Islamic approach.